Tidal tails of Milky Way globular clusters - Piatti, Andres Eduardo (2020)
We report on the search for overall kinematical or structural conditions that have allowed some Milky Way globular clusters to develop tidal tails. For this purpose, we built a comprehensive catalog of globular clusters with studies focused on their outermost regions and we classify the globular clusters in three categories: those with observed tidal tails, those with extra-tidal features that are different from tidal tails, and those without any signatures of extended stellar density profiles. When exploring different kinematical and structural parameter spaces, we found that globular clusters behave similarly, irrespective of the presence of tidal tails or any other kind of extra-tidal feature, or the absence thereof. In general, globular clusters whose orbits are relatively more eccentric and very inclined, with respect to the Milky Way plane, have undergone a larger amount of mass loss by tidal disruption. The latter has also accelerated the internal dynamics toward a comparatively more advanced stage of evolution. These outcomes show that it is not straightforward to find any particular set of parameter space and dynamical conditions that can definitely predict tidal tails along globular clusters in the Milky Way.